Effects of Potassium Chloride on a Metabolomic Path to Cardiovascular Disease and Diabetes. (29th May 2020) - Chatterjee, Ranee; Davenport, Clemontina; Kwee, Lydia; D'Alessio, David; Svetkey, Laura; Lin, Pao-Hwa; Slentz, Cris; Ilkayeva, Olga; Johnson, Johanna; Edelman, David; Shah, Svati
Abstract: Objectives: Metabolomic profiling is used to identify biological pathways and biomarkers for cardiovascular disease (CVD) and diabetes. Thus, metabolomics could be used to identify metabolic effects and demonstrate short-term efficacy of interventions designed to reduce longer-term risk of these conditions. Low potassium (K) intake has been linked to high blood pressure and increased CVD and diabetes risk. The effects of increasing K intake on metabolomic measures related to CVD and diabetes risk are not known. In this ancillary study, we tested the hypothesis that potassium chloride (KCl) supplementation would be associated with improvements in metabolomic biomarkers, such as branched-chain amino acids (BCAA) which are associated with CVD and diabetes risk. Methods: We performed targeted mass-spectrometry-based metabolomic profiling of 60 metabolites on baseline and 12-week (end-of-study) plasma samples from 26 African-American participants with prediabetes randomized to KCl supplements vs. placebo. Principal component analysis (PCA) was used for dimensionality reduction. Univariate and multivariable analyses were used to assess differences between the two intervention arms in the changes in metabolomic factor scores and individual metabolites. Results: In univariate comparisons, compared to placebo, a PCA factor composed of long-chain acylcarnitines (LCA) increased in the KCl arm ( P  = 0.02). In multivariable models adjusted for baseline factor score, age, and sex, this association with the LCA factor was no longer significant; but those taking KCl had significant reductions in the BCAA factor ( P  = 0.004) and in valine levels ( P  = 0.02). Conclusions: These results suggest that KCl supplementation may be associated with improvements in BCAA metabolism. Further studies among a larger population and with longer-term follow-up are warranted to verify these results and to determine if KCl supplementation may be an effective intervention for CVD and diabetes prevention. Funding Sources: NIH/Duke CTSA.